E-Module of Speech Listening Skills for BIPA 1 Learners for Children with Indonesian Culinary Content at the Cooperative Education Unit School - Arzaqi, Amalia; Idris, Nuny Sulistiany; Sundusiah, Suci (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this research is to describe 1) the needs analysis profile for the development of e-module listening-speech skills for BIPA 1 students with Indonesian culinary content; 2) the design of an e-module of listening-speech skills for BIPA 1 students with Indonesian culinary content; 3) developing an e-module of listening-speech skills for BIPA 1 students with Indonesian culinary content; and 4) the implementation of the listening-speech skills e-module for BIPA 1 students with Indonesian cuisine content. 5) Response of e-module on listening-speech skills for BIPA 1 students with Indonesian cuisine content. The research and development (R&D) approach was applied in this study with the ADDIE concept. Data collection techniques using literature study and semi-structured interviews. The research data is in the form of words and documents, which are then analyzed with the techniques that will be described descriptively in the form of a collection of words arranged, data reduction, analysis, data interpretation, and triangulation. According to the findings of this development research, the electronic development of the BIPA 1 students' listening-speech skills module with Indonesian cuisine content receives an average percentage of 87% with a very good predicate. As a result, the development of electronic listening-speech skills courses suited to the demands of BIPA 1 pupils is conceivable.